2003
DOI: 10.1073/pnas.0235560100
|View full text |Cite|
|
Sign up to set email alerts
|

Surface gas-exchange processes of snow algae

Abstract: The red-colored chlorophyte Chlamydomonas nivalis is commonly found in summer snowfields. We used a modified Li-Cor gas-exchange system to investigate surface gas-exchange characteristics of snow colonized by this alga, finding rates of CO2 uptake up to 0.3 μmol m−2⋅s−1 in dense algal blooms. Experiments varying the irradiance resulted in light curves that resembled those of the leaves of higher plants. Red light was more effective than white and much more effective than green or blue, because of the red astax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 23 publications
(25 reference statements)
1
36
1
Order By: Relevance
“…Only the younger cells from Ku¨htai, which still contained green parts of the chloroplast, not shaded by astaxanthin, indicated that some light dissipation took place (AZ/VAZ ¼ 0.27). Similar results relating to the light-dependence of photosynthesis in red snow algae was reported by Williams et al (2003) for North America. Rae et al (2000) described photosynthesis in Antarctic phytoplankton as temperature-dependent and showed similar kinetics to the data in Fig.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Only the younger cells from Ku¨htai, which still contained green parts of the chloroplast, not shaded by astaxanthin, indicated that some light dissipation took place (AZ/VAZ ¼ 0.27). Similar results relating to the light-dependence of photosynthesis in red snow algae was reported by Williams et al (2003) for North America. Rae et al (2000) described photosynthesis in Antarctic phytoplankton as temperature-dependent and showed similar kinetics to the data in Fig.…”
Section: Discussionsupporting
confidence: 75%
“…Earlier studies used different methods ( 14 C incubation or CO 2 gas exchange) and, with one exception (a study of a few green snow species in the former Czechoslovakia, Koma´rek et al, 1973), were carried out on algae from other continents, such as North America (Thomas, 1972;Mosser et al, 1977;Thomas & Duval, 1995;Williams et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For axis 1, the absolute value of climate variable scores exceeded 0.75 for all but FDSP, MSPK, and SFRD, which were the highest scoring variables for axis 2. that increases in the nonchromophoric fraction led to elevated DOC concentrations because light absorbance by lake water decreased and Secchi depth increased despite the elevated DOC concentrations. Possible sources of nonchromophoric DOC include in-lake algal and bacterial production (27), higher DOC inputs from more persistent snowfield microbial communities in years with longer snow seasons (28,29), and inputs of nonchromophoric DOC of allochthonous origin. Our observations of increasing DOC concentrations in lake water during mid-late summer periods in the 2000s, when the inflows of several lakes ceased to flow, support an interpretation that autochthonous production of nonchromophoric DOC by the plankton was important.…”
Section: Resultsmentioning
confidence: 99%